Pengaruh Kepemilikan Institusional, Kepemilikan Manajerial, Kinerja Keuangan, dan Women on Board Terhadap Pengungkapan Emisi Karbon - Barida Syava Noor Zahra; Christina Dwi Astuti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the effect of institutional ownership, managerial ownership, financial performance, and women on board on carbon emission disclosure. The research utilize secondary data in the form of annual reports and sustainability reports of the companies. The population of this study consists of companies in the energy, infrastructure, and industrial sectors listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The data collection method employed in this study is purposive sampling with unbalanced data. A total of 147 companies data points met the criterias. The data analysis method used is quatitative, utilizing SPSS 30 for multiple linear regression analysis. The results of this study indicate that financial performance has a positive effect on carbon emission disclosure, while institutional ownership, managerial ownership, and women on board have no effect on carbon emission disclosure